2022
DOI: 10.1037/pag0000694
|View full text |Cite
|
Sign up to set email alerts
|

Investigating age differences in the influence of joint attention on working memory.

Abstract: Previous research has demonstrated that older adults make limited use of social cues as compared to younger adults. This has been investigated by testing the influence of gaze cues on attentional processes, with findings showing significantly smaller gaze-cuing effects for older than younger adults. Here, we aimed to investigate whether this would also result in age-related differences in the influence of gaze cues on working memory (WM). We therefore tested the effects of gaze cues from realistic human avatar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 61 publications
3
6
0
Order By: Relevance
“…The results presented here align with, but also meaningfully extend, other recent research in this literature. For instance, Gregory and Kessler (2022) found that older adults show a memory advantage for objects that are looked toward (via both head turns and gaze shifts) relative to those that are looked away from, such that there are eye-gaze-to-item congruency effects on working memory that are equivalent for younger and older adults (Gregory & Kessler, 2022). They suggested that this age-related preservation of function may be due to the higher level of ecological validity used in their task relative to past research but did not directly manipulate the level of ecological validity in their study.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented here align with, but also meaningfully extend, other recent research in this literature. For instance, Gregory and Kessler (2022) found that older adults show a memory advantage for objects that are looked toward (via both head turns and gaze shifts) relative to those that are looked away from, such that there are eye-gaze-to-item congruency effects on working memory that are equivalent for younger and older adults (Gregory & Kessler, 2022). They suggested that this age-related preservation of function may be due to the higher level of ecological validity used in their task relative to past research but did not directly manipulate the level of ecological validity in their study.…”
Section: Discussionmentioning
confidence: 99%
“…It is clearly the case, though, that measures of social attention are a significant part of the reliable operational diagnostic definition of the preschool phenotype of autism (Mundy & Bullen, 2022). Moreover, beyond the preschool period, social attention can also be reliably and validly measured in children, adolescents and adults with typical development and autism (e.g., Bayliss et al, 2013; Freeth et al, 2020; Freeth & Bugembe, 2019; Gregory & Kessler, 2022; Grynszpan et al, 2019; Mundy et al, 2016; Nowell et al, 2020; Oberwelland et al, 2016), as well as among individuals who exhibit the broad autism phenotype (Elsabbagh et al, 2009; Morgan et al, 2023; Nayar et al, 2022; Swanson et al, 2013; Swanson & Siller, 2014; Zhao et al, 2017). Recent research also suggests that social attention measures may be sensitive to sex differences in autism (Charwarska et al, 2016; Harrop et al, 2020).…”
Section: The Hypothetical Construct Of Social Attention In Autism Res...mentioning
confidence: 99%
“…Individuals tend to remember the item that is important for their goals (Altmann and Trafton, 2002;Montagrin et al, 2013). For example, although older adults show a decline in the gaze cueing effect, they still utilized gaze cues to facilitate memory encoding (Gregory and Kessler, 2022). In other words, older adults would like to follow the gaze cues to serve a goal-directed process rather than the uninformative cues.…”
Section: Mechanism Of Gaze Cueing Effects On Memorymentioning
confidence: 99%
“…For example, if researchers used the transcranial electric stimulation (tES) techniques (Živanović et al, 2022) to establish a relationship between the brain region of processing intention information and arrow cues in vWM task, the arrow cues would enhance individuals vWM performance as a manner of gaze cues did? In future studies, researchers should employ cognitive neuroscience techniques (e.g., neuroimaging and brain stimulation) to explore the critical difference between gaze and arrow cues (Gregory and Kessler, 2022), which will help us understand the social nature of gaze cues. Additionally, an interesting direction for the following research is to determine the gaze cues in more real-world surroundings.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
See 1 more Smart Citation